Correction to: The association between premorbid beta blocker exposure and mortality in sepsis-a systematic review - Tan, Kaiquan; Harazim, Martin; Tang, Benjamin; Mclean, Anthony; Nalos, Marek (Critical care, 2020)
In the publication of this article [1], there was an error in the cited reference 23 [2] within the Family Name. This has now been updated in the original article.